Childhood occasional hypertension and its association with size at birth and early growth: a population-based retrospective cohort study from China - Shuang Zhang; Leishen Wang; Tao Zhang; Yijuan Qiao; Wei Li; Weiqin Li (Italian Journal of Pediatrics)
Abstract Background Hypertension has recently shown a rapid rise in prevalence among children and adolescents. It can track into adulthood and tend to manifest at an earlier age. It should be prevented urgently and efficiently. Methods This study assesses the prevalence of occasional hypertension (OHTN) at 5 ~ 6 years old and evaluates its association with size at birth and BMI at 2 and 5 ~ 6 years old in full-term children. We conducted a population-based cohort study of 12,564 children from 66 kindergartens in Tianjin, China. Information on birth weight, body mass index (BMI) at 2 and 5 ~ 6 years old, and blood pressure at 5 ~ 6 years old was retrospectively collected. Results The prevalence of childhood OHTN (SBP or DBP ≥ P95 percentile for sex, age, and height) was 17.0%. At birth, SGA has a high risk of OHTN (AOR 1.36, 95%CI 1.10–1.68). In the SGA subgroup, although children are of normal weight at 5 ~ 6 years old, excessive catch-up growth (BMI ≥75th at 2 years old) was still attributed to OHTN (OR 1.51, 95%CI 1.03–2.24). Obesity (BMI ≥2SD at 5 ~ 6 years old) was a vital risk factor for OHTN (AOR 2.93, 95%CI 2.56–3.36) unregarding with birthweight (OR 95%CI: SGA 3.23(1.66 ~ 6.27), AGA 2.83 (2.42–3.31), LGA 3.52 (2.65–4.68)). The co-presence of moderate or excessive catch-up growth before 2 years old and obesity at 5 ~ 6 years old significantly increased the risk of childhood OHTN (OR from 2.74 (1.65–4.54) to 6.53 (2.68–15.90)). Conclusions Preschool obesity, low birth weight, and excessive catch-up growth increased the risk of OHTN in childhood.